Diagnostic value of cfDNA and long fragment DNA in patients with breast cancer - Xu, Haiyan; Liu, Guirong (Cellular and Molecular Biology, 2020)
To investigate the diagnostic value of cell-free DNA (cfDNA) and long fragment DNA in breast cancer patients.Female patients with breast cancer (n = 80) were recruited over one year for this study, and served as an observation group. The control group consisted of 50 normal, healthy females. Plasma levels of cfDNA and long fragment DNA were determined a day before treatment, 7 days after treatment, and on the 20th day of treatment. The levels of cfDNA and long fragment DNA in breast cancer patients before treatment were significantly higher than those of the control group (p<0.05). Patients cfDNA and long fragment DNA levels 7 days after treatment were not significantly different from the corresponding values at 1 day before treatment (p>0.05), but they decreased significantly on the 20th day of treatment, when compared with levels before treatment (p<0.05). Before treatment, the optimal cut-off point for cfDNA in patients’ peripheral blood, sensitivity, specificity and accuracy were 12.25ng/mL, 79.12%, 86.15%, and 73.32%, respectively. The area under the ROC curve (AUC) was 0.865 (95% CI = 0.754-0.903). Close monitoring of cfDNA levels in peripheral blood of breast cancer patients in real-time can be used for early diagnosis of the disease.